Ax + by = a - b bx - ay = a+ b by elimination
2 answers:
Answer: x = 1, y = -1
Step-by-Step Explanation:
As the answer involves many steps, I’ve taken a pic of my working. Please check the attached photo.
![ax + by = a - b \: \: \: ...(i)\\ \\ bx - ay = a+ b \: \: \: ...(ii) \\ \\](https://tex.z-dn.net/?f=ax%20%2B%20by%20%3D%20a%20-%20b%20%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20...%28i%29%5C%5C%20%20%5C%5C%20bx%20-%20ay%20%3D%20a%2B%20b%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20...%28ii%29%20%5C%5C%20%20%5C%5C%20)
Multiply equation (i) with a and equation (ii) with b ,
![{a}^{2} x + aby = {a}^{2} - ab \: \: \: ...(iii)\\ \\ {b}^{2} x - aby = ab + {b}^{2} \: \: \: ...(iv)](https://tex.z-dn.net/?f=%20%7Ba%7D%5E%7B2%7D%20x%20%2B%20aby%20%3D%20%20%7Ba%7D%5E%7B2%7D%20%20-%20ab%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20...%28iii%29%5C%5C%20%20%5C%5C%20%20%7Bb%7D%5E%7B2%7D%20x%20-%20aby%20%3D%20ab%20%2B%20%20%7Bb%7D%5E%7B2%7D%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20...%28iv%29)
Adding (iii) and (iv) , we get ,
![( {a}^{2} + {b}^{2} )x = {a}^{2} + {b}^{2} \\ \\ x = 1](https://tex.z-dn.net/?f=%28%20%7Ba%7D%5E%7B2%7D%20%20%2B%20%20%7Bb%7D%5E%7B2%7D%20%29x%20%3D%20%20%7Ba%7D%5E%7B2%7D%20%20%2B%20%20%7Bb%7D%5E%7B2%7D%20%20%5C%5C%20%20%5C%5C%20x%20%3D%201)
Now , from (i) ,
![ax+by=a−b \\ \\ a+by=a−b\\ \\ by=−b \\ \\ y=−1](https://tex.z-dn.net/?f=ax%2Bby%3Da%E2%88%92b%20%5C%5C%20%20%5C%5C%20a%2Bby%3Da%E2%88%92b%5C%5C%20%20%5C%5C%20by%3D%E2%88%92b%20%5C%5C%20%20%5C%5C%20y%3D%E2%88%921)
You might be interested in
Answer:
4 pepperoni pizzas
Step-by-step explanation:
2(4x - 7) -1 = 11
8x - 14 -1 = 11
8x - 15 = 11
+ 15 + 15
8x = 26
/8 /8
x = 3. 25 ------> Rounded: 3.30
The answer should be 6 bro
Answer: (n+5)x(n+1)
Step-by-step explanation:
1. Write 6n as a sum
2. Factor out n form the expression
3. Factor out n+5 from the expression
(n+5)x(n+1)
Step-by-step explanation:
The answer is scalene triangle